2005
DOI: 10.1557/jmr.2005.0010
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Al2O3/BN Nanocomposites by Chemical Processing and Their Mechanical Properties

Abstract: Al2O3/BN nanocomposites were fabricated through a novel chemical route involving hot-pressing of α–Al2O3 powders covered partly with turbostratic BN (t-BN). The nano-sized hexagonal BN (h-BN) particles were found to be homogeneously dispersed within the Al2O3 grains as well as at grain boundaries, which is indicative of nanocomposite structures. Thus, the present nanocomposites exhibited the unique properties of high strength and low Young’s modulus associated with nanocomposites. This paper discusses in detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 15 publications
2
37
0
2
Order By: Relevance
“…Room temperature mechanical properties of Al 2 O 3 /h-BN refractories samples were investigated, and the results are depicted in Table II. The results show that fracture strength r f , Young's modulus E, fracture toughness K IC , and work of fracture c WOF were all decreased with the increase of h-BN content fraction, as also observed by Rutkowski et al [19] and Kusunose et al [31] The mechanical properties were closely associated with the physical properties such as AP and BD. The variation trend of the BD was same as that of the mechanical properties and these observations were in accordance with previous studies.…”
Section: A the Phase Composition And Microstructuresupporting
confidence: 77%
“…Room temperature mechanical properties of Al 2 O 3 /h-BN refractories samples were investigated, and the results are depicted in Table II. The results show that fracture strength r f , Young's modulus E, fracture toughness K IC , and work of fracture c WOF were all decreased with the increase of h-BN content fraction, as also observed by Rutkowski et al [19] and Kusunose et al [31] The mechanical properties were closely associated with the physical properties such as AP and BD. The variation trend of the BD was same as that of the mechanical properties and these observations were in accordance with previous studies.…”
Section: A the Phase Composition And Microstructuresupporting
confidence: 77%
“…Thus, it is concluded that the observed high strength of SiCBN nanocomposites is attributable mainly to the reduction of the critical flaw size by the nano-sized h-BN dispersion. The mechanical properties of h-BN dispersed nanocomposites [23][24][25][32][33][34] are summarized in Table. 1. It is found that all the produced h-BN dispersed nanocomposites have the unique mechanical property of high strength though low Young's modulus.…”
Section: Microstructure Of Sicbn Nanocompositesmentioning
confidence: 99%
“…Thus, we proposed a simple chemical process for precipitating an h-BN precursor, which is soluble in any ball-milling solvent and can readily transform into h-BN on matrix particles. [23][24][25] Boric acid and urea are very suitable as boron and nitrogen sources for h-BN, respectively. Figure 1 shows a conceptual schematic of the chemical process.…”
Section: Introductionmentioning
confidence: 99%
“…18 Kusunose et al fabricated Al 2 O 3 /BN composite through an in-situ chemical route. Nano-sized BN particles are homogeneously dispersed in the Al 2 O 3 grains as well as at the grain boundaries, and the strength and the fracture toughness were all improved by the nano-sized BN 19 . Machinable B 4 C/BN composite was prepared via an in-situ hotpressing process by Jiang et al In their work, the strength and fracture toughness of the composite with BN content of 10 wt% and 20 wt% achieved high values that are comparable to or even higher than those of the monolithic B 4 C. 20 A number of other BN containing ceramic composites involving SiAlON/BN, 21 Si 3 N 4 /BN, 22 ZrB 2 /SiC/BN, 23 SiC/BN, 24,25 AlN/BN, 26 and ZrO 2 /BN, 27 have also been prepared by in-situ reactions.…”
Section: Introductionmentioning
confidence: 99%